2021
DOI: 10.3389/fmicb.2020.598024
|View full text |Cite
|
Sign up to set email alerts
|

Maipomycin A, a Novel Natural Compound With Promising Anti-biofilm Activity Against Gram-Negative Pathogenic Bacteria

Abstract: Pathogenic bacterial biofilms play an important role in recurrent nosocomial and medical device-related infections. Once occurred, the complex structure of the biofilm promotes the development of antibiotic resistance and becomes extremely difficult to eradicate. Here we describe a novel and effective anti-biofilm compound maipomycin A (MaiA), which was isolated from the metabolites of a rare actinomycete strain Kibdelosporangium phytohabitans XY-R10. Its structure was deduced from analyses of spectral data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Quorum sensing inhibitors can be applied along with other antibiotics such as Isobutyl-4, 5-Dihydroxy-2, 3-pentanedione (DPD) and phenyl-DPD with gentamicin and small molecules to fight biofilm-mediated drug resistance [ 60 ]. A recent study found that maipomycin A, a novel natural compound with promising anti-biofilm activity against pathogenic GNB, acts as a synergist to enhance colistin efficacy against A. baumannii [ 121 ]. In situations where antimicrobial treatment has been unsuccessful or where current therapies have caused resistance, iron-chelation therapy reduces the growth of MDR-GNB and potentiates antimicrobial strategies, particularly in HAP/VAP [ 122 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quorum sensing inhibitors can be applied along with other antibiotics such as Isobutyl-4, 5-Dihydroxy-2, 3-pentanedione (DPD) and phenyl-DPD with gentamicin and small molecules to fight biofilm-mediated drug resistance [ 60 ]. A recent study found that maipomycin A, a novel natural compound with promising anti-biofilm activity against pathogenic GNB, acts as a synergist to enhance colistin efficacy against A. baumannii [ 121 ]. In situations where antimicrobial treatment has been unsuccessful or where current therapies have caused resistance, iron-chelation therapy reduces the growth of MDR-GNB and potentiates antimicrobial strategies, particularly in HAP/VAP [ 122 ].…”
Section: Introductionmentioning
confidence: 99%
“…This compound showed strong anti-biofilm activities against Gram-negative bacteria including Acinetobacter baumannii ATCC 19606 and Pseudomonas aeruginosa ATCC 27853 with MBIC values of 8 and 32 mg/mL, respectively. More interestingly, it has demonstrated that this natural product might exert its antibiofilm activity through chelating irons [39].…”
Section: Alkaloidsmentioning
confidence: 99%
“…crude cell-free supernatants ( 274 ). Maipomycin A which is isolated from the metabolites of the marine actinomycete and acts as an iron chelator inhibits A. baumannii biofilm formation on medical materials including silicone catheters and endotracheal tubes (polyvinyl chloride) ( 275 ). Several sets of compounds derived from marine sponges showed inhibition of different bacterial biofilm including A. baumannii specifically through non-microbicidal mechanisms ( 276 ).…”
Section: Strategies Of Preventing a Baumannii Biof...mentioning
confidence: 99%